African Journal of Political Science / Revue Africaine de Science Politique (JSTOR)
The AJPS is published by the African Association of Political Science (AAPS), with the aim of providing a platform for African perspectives on issues of politics, economy and society in Africa. It is published 2 times a year - in June and December, and targeted at the social science community, policy-makers, and university students
Keywords: African Studies